Pengaruh Kepuasan Kerja dan Loyalitas Kerja Terhadap Turnover Intention PT Sumber Alfaria Trijaya. Tbk Kecamatan Karawang Barat - Rosmawati Suhartina, Dhinda; Wanta, Wanta; Darojatul Romli, Asep (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to find out and assess the effect of job satisfaction and job loyalty on employees' intention to leave their current workplace. PT Sumber Alfaria Trijaya. Tbk, became the object of this research which is located in West Karawang. The method used in this research is kunatitatif type with verification analysis techniques. The sampling method used is saturated sampling, with a total of 105 responses received from the total number of participants. In analysing the research data, multiple linear regression analysis was used for this study. from the results of the research found that at PT Sumber Alfaria Trijaya. Tbk, job satisfaction and job loyalty have a simultaneous and partial impact on the desire to leave the current job and look for a new job elsewhere. The level of job satisfaction and loyalty that a person has towards his company has a positive relationship with the desire to leave his current job. About 13% of the results generated by this model are influenced by external variables.